GAMBARAN EFEK SAMPING PEMBERIAN KONTRASEPSI SUNTIKAN HORMONAL - Andi Hariati; Nur Ekawati; Nelly Nugrawati (Journal Of Midwifery And Nursing Studies, 2020)
Delaying pregnancy is an effort to prevent conception, this can be used with a contraceptive method, including using hormonal injections. Hormonal injection contraception has several side effects, therefore the purpose of this study was to determine the side effects of giving hormonal contraception in the form of weight gain, menstrual disorders and the occurrence of dizziness, nausea and vomiting. This study uses a literature study research design, namely by conducting a study of previous studies with the same title to get a comparison of the results of previous studies. With the discussion obtained from journals that all studies used were the hormonal content of the DMPA contraceptive stimulates the appetite control center in the hypothalamus. Injectable contraceptives contain Depoprogestin which stimulates the hormone progesterone so that it can change the speed of egg delivery in the fallopian tube, the endometrium becomes thin and atrophic with reduced glandular activity which causes the menstrual cycle not to run smoothly. Some DMPA injection contraceptives will experience side effects, namely dizziness/headache, which occurs as a result of the hormone progesterone which will create a hormonal imbalance that triggers headaches. The conclusion is that hormonal injection contraceptives can cause side effects of weight gain, menstrual disorders and dizziness, nausea and vomiting.